Multilayer porous sintered film and filter assembly
By selecting different metal particle layers with similar sintering shrinkage characteristics during the sintering process, a multi-layer porous sintered metal film is produced, which solves the problem of unstable supercritical fluid filtration equipment under high pressure and high temperature in the prior art, and achieves high efficiency , durable filtering effect.
Patent Information
- Application Number
- CN202323077187.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-14
- Filing Date
- 2023-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2033-11-14
AI Technical Summary
The prior art is difficult to efficiently filter supercritical fluids, such as supercritical carbon dioxide, at high pressures and high temperatures, resulting in unstable and poor durability of filter equipment and components over their service life.
A multi-layer porous sintered metal film is used to produce a stable film by selecting different metal particle layers with similar sintering shrinkage characteristics during the sintering process. The film consists of a coarse layer and a fine layer made of microparticles, and the fine layer is made of nanoparticles, which bind the particles on the surface by a sintering step to form an interconnected metal matrix.
It realizes a stable and durable filtration effect under high pressure and high temperature, improves the overall strength and fluidity of the membrane, and can effectively remove impurity particles in the fluid.
Smart Images

Figure CN222492169U_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a porous sintered metal membrane, which includes multiple layers made of different metal particles and can be used as a filtration membrane, and also to methods of making and using the porous sintered metal membrane. Background Art
[0002] Porous sintered metal bodies can be used in a variety of industrial applications, including use as filters to remove impurities from fluids used in manufacturing. Many manufacturing processes require extremely pure fluids as raw materials or processing fluids. For example, many different stages of semiconductor and microelectronic device manufacturing require the use of high-purity gases or liquids as raw materials, as well as high-purity processing fluids for steps such as cleaning, etching, and other surface manufacturing. In order to provide high-purity fluids in the manufacturing process, filters are often used to remove contaminants from the fluid before the fluid is used immediately.
[0003] The fluid may be in the form of a gas or liquid, or in the form of a supercritical fluid. Supercritical carbon dioxide has a variety of uses in industry, including cleaning and solvent extraction applications. High-purity, supercritical carbon dioxide can be used in the electronics and semiconductor manufacturing industries, which require extremely high cleanliness and material purity. In one such application, supercritical carbon dioxide can be used to remove photoresist materials from the surface of semiconductor wafers. Typically, the supercritical carbon dioxide supplied is filtered before use to be free of particulate impurities at a low nanometer level, for example by filtering to remove particles in the size range of 10 or 20 nanometers or less.
[0004] Carbon dioxide (CO2) exists as a supercritical fluid at temperatures and pressures above its critical temperature (31.10°C, 87.98°F, 304.25K) and critical pressure (7.39 MPa, 72.9 atm, 1,071 psi, 73.9 bar). Typical operating conditions for the process of filtering supercritical carbon dioxide include temperatures exceeding 70, 90, or 100 degrees Celsius and pressures exceeding 25, 30, 35, or 40 MPa.
[0005] Equipment for handling and filtering supercritical carbon dioxide must be designed to survive and operate under the temperature and pressure required for maintaining carbon dioxide in the supercritical state. These conditions are obviously more harsh than the conditions for filtering many other types of industrial raw materials or process fluids. Many filtering steps of other fluids occur at ambient temperature or at a temperature that is only slightly elevated, and under a pressure that is roughly atmospheric pressure, slightly higher than atmospheric pressure or far below atmospheric pressure. Therefore, it is particularly challenging to develop new, useful and improved methods and equipment for filtering supercritical fluids (such as supercritical carbon dioxide), because equipment and components (such as filter membranes) must be stable and durable in an effective service life at relatively high pressures and temperatures. Summary of the invention
[0006] The following describes a porous sintered metal membrane that can be used as a filter membrane for filtering a fluid stream to remove impurities from the fluid. Also described are methods for making the porous sintered metal membrane and methods of using the porous sintered membrane to filter a fluid stream.
[0007] Porous metal membranes are typically made by techniques that include forming a thin compressed body from metal particles and sintering the compressed body to fuse the particles together at their surfaces. These particles typically include particles on the nanometer scale, referred to as "nanoparticles" because the nanoparticles can produce membranes with nanometer-scale pores. Various techniques use a compression step at extremely high pressures, such as thousands of pounds per square inch, which results in a relatively dense compressed membrane, for example, with a porosity ("void space") of less than 20%.
[0008] A filter membrane with a higher porosity may be preferable to a membrane with a lower porosity for various applications if a useful balance of properties can still be achieved. The effectiveness of a filter membrane in removing particles from a fluid can be measured by properties including bubble point, flux, and rejection. Bubble point is a property associated with the pore size of the membrane. The higher the bubble point, the smaller the pores and the better the filtration characteristics. Flux is a measure of the flow rate that can pass through the membrane. High flux and relatively high flow rates may be desirable and may be associated with relatively high porosity. Rejection refers to the number of impurity particles in a fluid that are removed by the filter membrane (expressed as a percentage). The filter membrane must exhibit a level of rejection that is useful in commercial applications. Ideally, a filter membrane used to filter supercritical carbon dioxide will exhibit a high bubble point (associated with a small pore size) as well as a high flow rate (associated with a relatively high porosity).
[0009] When sintered films are produced by techniques including sintering a compressed body, the step of sintering the film sometimes produces unbalanced forces, which can lead to physical instability and the possibility of film rupture. During the sintering process, bonds between the surfaces of the metal particles are formed by the movement of material between the surfaces. Associated with the formation of bonds between the particle surfaces is a reduction in the volume of the sintered body, known as "sintering shrinkage." Sintering shrinkage of a metal body with different layers shrinking at different rates can produce internal stresses in the layers or body, which can lead to body rupture.
[0010] Various methods have been used to reduce the tendency of a multilayer body to crack during sintering. By one technique, different layers of a multilayer body share at least one type of particle (based on size and chemical composition) between the layers to increase the uniformity of the layers and produce similar sintering shrinkage in the two layers. In example films and methods, an amount of coarse particles (particles having an average size greater than 1 micron, such as greater than 5 or 20 microns) used to form the coarse layer can be added to the fine layer so that the two layers have similar shrinkage characteristics during sintering.
[0011] According to the membranes and methods, a membrane that is stable during sintering can be manufactured by a new technique that selects metal particles with similar sintering shrinkage characteristics for different layers without adding a certain amount of particles of the coarse layer to the fine layer. Advantageously, the fine layer can be made entirely or almost entirely of nanoparticles, which allows the fine layer to be manufactured to have a relatively high porosity and high fluidity, as well as small pores and a high bubble point. Based on the sintering points of the different particles, similar shrinkage characteristics of the particles of the different layers can be achieved. In the example methods and membranes, the fine particles of the fine layer can have a sintering point that is higher than the sintering point of the coarse particles of the coarse layer.
[0012] In one aspect, the present specification relates to a multilayer porous sintered membrane, the membrane comprising: a coarse layer comprising sintered micron particles, the micron particles having micron particle sintering points, the coarse layer having coarse layer porosity; and a fine layer comprising sintered nanoparticles, the nanoparticles having nanoparticle sintering points, the fine layer having fine layer porosity, the nanoparticle sintering points being greater than the microparticle sintering points, and the fine layer porosity being greater than the coarse layer porosity.
[0013] In another aspect, the present disclosure relates to a method. The method comprises: compressing micron particles into a coarse layer using a first compression pressure, the micron particles having a micron particle sintering point; and forming a fine layer on the coarse layer by applying nanoparticles to the coarse layer and compressing the nanoparticles using a second compression pressure lower than the first compression pressure to form a precursor including the coarse layer and the fine layer. The nanoparticles have a nanoparticle sintering point greater than the microparticle sintering point. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 An example multilayer film is shown as described.
[0015] Figure 2A , 2B 2C are scanning electron microscope images of examples of the described multilayer films.
[0016] Figure 3A and 3B is a scanning electron microscope image of an example of the described multilayer film.
[0017] Figure 4 is an example of a filtration device comprising the described multilayer membrane.
[0018] Figure 1 and 4 are schematic and not necessarily drawn to scale. DETAILED DESCRIPTION
[0019] Novel porous sintered metal membranes (e.g., "porous membranes," "porous sintered membranes," or sometimes simply "membranes" herein) that can be used as filter membranes for filtering fluid streams to remove impurities from the fluid are described below. Novel and inventive methods for making the described porous sintered membranes are also described, as well as novel and inventive methods for filtering fluid streams using the described porous sintered membranes.
[0020] The porous sintered membrane is in the form of a porous metal body containing (at least) two layers made of sintered metal particles: a first layer mainly or completely derived from coarse metal particles referred to herein as "coarse particles" or "microparticles", and a second layer mainly or completely derived from fine metal particles referred to herein as "fine particles" or "nanoparticles". Each layer is made of a metal matrix containing metal particles interconnected at the particle surface by a sintering step.
[0021] The first layer (sometimes called the "support layer" or "coarse layer") has larger pore openings and lower porosity than the second layer, and acts as an integral part of the overall support structure of the multilayer membrane while still allowing good flow characteristics through the membrane. The second layer (sometimes called the "filtration layer" or "fine layer") has smaller pore openings and higher porosity than the support layer, acts as a filtration layer, and can increase the overall strength of the membrane.
[0022] The two layers of the membrane are made of different types of metal particles. The support layer is made of relatively large particles called "coarse" particles, and the filtration layer is made of smaller particles called "fine particles" or "nanoparticles." Based on the construction of the two layers, the membrane can exhibit useful or advantageous performance characteristics as a filtration membrane. The relatively small pores of the filtration layer produce a relatively high bubble point. However, the filtration layer also has a relatively high porosity, which allows for good flow through the membrane and a desirable or advantageous combination of a high bubble point and high flowability.
[0023] A novel method of making a multilayer film is also described. A useful method forms a precursor containing two layers, one made of fine particles and the other made of coarse particles. The precursor can be processed by sintering the multilayer precursor with a single sintering step that causes the particles of the two layers to sinter simultaneously and prevents the film from cracking during sintering.
[0024] During the sintering step, the metal particles of the precursor are bonded together at adjacent surfaces by heating the precursor to fuse the metal at adjacent surfaces together. The transfer of metal between adjacent particle surfaces to form bonds can also cause the precursor film to change in size in the form of "sintering shrinkage". Due to the diffusion of metal from adjacent particles, bonds or "bridges" are formed between particles, and the size of the particles changes slightly, causing the precursor to shrink (i.e., "sintering shrinkage"). If different layers of a multilayer film exhibit different shrinkage rates during the sintering process, the uneven rate of dimensional change of different layers can cause the film to rupture.
[0025] To prevent cracking that can occur from sintering shrinkage, the novel multilayer film can be made by forming different layers from different metal particles, where the different metals are selected to exhibit similar amounts of dimensional change ("sintering shrinkage") during sintering. The metal particles of the fine layer and the metal particles of the coarse layer are selected so that the different layers shrink at similar rates during sintering and are less susceptible to force imbalance and cracking.
[0026] The shrinkage characteristics of the different layers can be controlled by selecting particles of the two different film layers with different sintering points. For example, in order to provide different layers with shrinkage characteristics that are similar enough to avoid cracking due to sintering shrinkage, the particles of the coarse layer can have a sintering point lower than the sintering point of the particles of the fine layer.
[0027] In addition, sintering shrinkage may be affected by the amount of contact between adjacent particles of the precursor that form a bond or "bridge" between contacting surfaces. The amount of contact between particles of the precursor may be affected by the amount of pressure used to compress the particles to form the precursor. As described herein, the nanoparticles of the precursor can be compressed at relatively low pressures to produce low or minimal contact between the nanoparticles of the precursor; the amount of contact between the compressed nanoparticles of the fine layer can be sufficient to form a cohesive precursor that can also be formed into a fine layer of the film by the sintering step, but does not need to be significantly greater. In contrast, the micron particles of the coarse layer can be compressed at relatively high pressures to form a higher amount of contact between the coarse particles, and sintering is enhanced.
[0028] Based on the foregoing, the various features of particles and the compression step can be used to provide the desired porous sintered film. For the thin layer, the nanoparticles whose diffusion activity is lower than the coarse particles of the coarse layer can be selected, that is, compared with the sintering temperature of the coarse particles, the nanoparticles can have a higher sintering temperature. In addition, the nanoparticles can be formed into precursors by pressing the nanoparticles under relatively low or minimized pressure, so that the diffusion of the metal between the contact particle surfaces is subject to the restriction of a relatively small number of contact points between the compressed nanoparticles of the precursor. In addition, the sintering of the coarse layer is subject to the use of a relatively high compression pressure to form the coarse layer precursor to form a larger number of contact surfaces between micron particles. These factors can be applied to the particles of the precursor to produce two layers (thin layer and coarse layer) of a multilayer precursor, and these two layers will shrink at a similar rate during sintering to prevent the film from breaking during sintering.
[0029] The porous sintered membrane described is a porous metal structure that includes a metal matrix (or simply "matrix") that originates from metal particles and is therefore described as "comprising" metal particles (e.g., including, consisting of, or consisting mainly of metal particles) that are connected together (e.g., "interconnected") on their surfaces by a step of sintering the particles (i.e., "sintered metal particles"). By the step of sintering a precursor containing a metal particle layer under unsintered, compressed conditions, the particles are fused together on their surfaces to form an interconnected matrix.
[0030] As used herein, the term "sintering" has a meaning consistent with that given to such term when used in the field of porous sintered metal structures, such as porous sintered metal membranes of the type that can be used as metal filtration membranes. Consistent with this, the term "sintering" can be used to refer to the process of bonding (e.g., "welding" or "fusing") together a collection of one or more small metal particles of different types (size, composition, shape, etc.) by applying heat to an unsintered precursor containing the particles, so that the particles reach a temperature that enables the particles to fuse together through metallic bonds formed between the surfaces of adjacent particles, but does not cause the particles to melt, that is, the metal particles subjected to sintering do not reach a melting temperature and do not become a flowable liquid.
[0031] As used herein, the "sintering point" of an assembly of metal particles refers to the temperature at which the particles within the assembly begin to adhere to each other at an appreciable rate, i.e., the temperature at which the particles in the assembly begin to fuse together at contact surfaces without melting to form a porous interconnected matrix under a particular pressure, such as atmospheric pressure. Unless otherwise specified, the sintering points and sintering temperatures described are given for a process performed with the particles under atmospheric pressure conditions and without external pressure being applied to the particles.
[0032] Each of the fine particles used to form the fine layer and the coarse particles used to form the coarse layer has a characteristic sintering point. According to certain example methods and membranes, the sintering point of the fine particles can be higher than the sintering point of the coarse particles. The difference between the sintering point of the fine particles and the sintering point of the coarse particles can be at least a few degrees Celsius, or can be a relatively large difference, such as a difference of at least or greater than 20, 50 or 100 degrees Celsius. The sintering points of the example fine particles and coarse particles of the porous sintered membrane can differ by at least 1 or 2 degrees Celsius, or by less than or greater than 20, 50 or 100 degrees Celsius.
[0033] The collection of particles can be processed by sintering in an effective temperature range that includes the sintering point and above the sintering point but below the melting temperature of the particles. The temperature range that can be used to sinter the fine particles includes the temperature range that can also be used to sinter the coarse particles. In a useful method, all or substantially all of the metal particles of the fine layer and the coarse layer can be sintered at a single sintering temperature that can be used in a single sintering step.
[0034] The useful sintering point of each type of particle can be a typical sintering point of known metal particles, such as a temperature above 700, 800 or 1000 degrees Celsius. The temperature of the sintering step (i.e., "sintering temperature") for making the specific membrane having particles of different chemical compositions, sizes and different sintering points will be a sintering temperature that is higher than the sintering point of the two types of particles and lower than the melting temperature of the two types of particles. The preferred sintering temperature may be in the middle part of the temperature range that can effectively sinter the two types of particles. Sintering temperatures within this range can avoid excessive flow or deformation of different particles during the sintering process, which may affect (reduce) the final porosity of the sintered layer. Sintering temperatures in the middle part of the useful sintering temperature range can effectively produce a multilayer sintered membrane having the described fine layer porosity (relatively high) and pore size (relatively low) characteristics, and the support layer has the described porosity.
[0035] The multilayer porous sintered membrane comprises two identifiable parts or "layers" made of different types of metal particles. Without limiting the functions of the different layers, the first layer is sometimes referred to herein as a "coarse layer" or "support layer", and the second layer is sometimes referred to as a "fine layer" or "filtration layer". The coarse layer can be made mainly or entirely of coarse metal particles, for example, the coarse metal particles account for at least 50%, 60%, 70%, 80%, 90% or 99% of the total weight of the coarse layer. The fine layer can be significantly or entirely made of "fine" metal particles or "nanoparticles", for example, the fine metal particles account for at least 90%, 95% or 99% of the total weight of the fine layer.
[0036] As part of a multilayer porous sintered membrane (or precursor, see below), the two different layers can be visually inspected using magnification. A coarse layer made primarily or entirely of coarse particles can be observed as containing only or primarily coarse particles bonded together at the particle surface by the sintering step. A fine layer made predominantly or entirely of fine particles will be observed as containing entirely or almost entirely fine particles bonded together at the particle surface by the sintering step. The coarse layer will have a lower porosity than the fine layer. The fine layer will have a smaller pore size than the coarse layer.
[0037] Non-limiting examples of metal particles that can be used as micron particles of the coarse layer include metal particles made of any metal (including pure metals and alloys), such as stainless steel, another iron or steel alloy, nickel or nickel alloy, titanium or titanium alloy, etc. According to a specific example film, the coarse layer can be made of particles that all contain or consist of the same type of metal (e.g., stainless steel) (e.g., include, consist of, or mainly consist of the particles), for example, the collection of micron particles used to make the coarse layer can contain at least 80 weight %, 90 weight %, 95 weight % or 99 weight % of particles made of the same metal material, such as stainless steel particles, accounting for the total weight of the coarse layer micron particles.
[0038] The micron particles used to form the filter layer start in the form of a collection of micron particles, which have one or more common general physical characteristics, such as shape, size and chemical composition. The collection of micron particles is essentially dry and flowable, and most or all of the particles are similar or identical in composition, such as made of a single type of metal (including alloys).
[0039] The collection of microparticles used to form the coarse layer may all have a similar shape, or alternatively, may include microparticles having two or more different shapes (e.g., granular, elongated, fibrous, or dendritic). The collection of microparticles may have a size that fits a single particle size distribution in the shape of a bell curve, e.g., is "monomodal," or alternatively, may have a size that defines two different particle size distributions, i.e., the collection may have a bimodal particle size distribution.
[0040] Useful micronized particles may have a "granular" shape, meaning that the particle is an individual particle that can be considered spherical, unbranched, and non-elongated, e.g., having flat or rounded surfaces and corners or edges that may be rounded or angled. Granular particles are unbranched, non-dendritic, and have an aspect ratio of less than 5, or less than 3, or less than 1.5.
[0041] An example of a useful micron particle set for forming a coarse layer can be made of micron particles of a single type of metal that are substantially all granular (e.g., include, consist of, or consist mainly of said micron particles). An example set includes micron particles (e.g., include, consist of, or consist mainly of) having a particle size distribution in the form of a "normal" or "Gaussian" distribution curve in a single unimodal state and an average particle size (D50) greater than 1 micron. An example of a useful average particle size of a micron particle set can be 1 micron to 100 microns, such as 1 micron to 20 microns or 1 micron to 5 or 10 microns. The particle size of the metal particles can be measured by ASTM B822-17 (Standard Test Method for Particle Size Distribution of Metal Powders and Related Compounds by Light Scattering).
[0042] According to other example films, the coarse layer may be made of a collection of microparticles having a granular shape (at least 80%, 90%, 95% or 99% of the microparticles are granular) and having a bimodal particle size distribution (e.g., including, consisting of or mainly consisting of the collection of microparticles). The collection contains two different granular microparticle collections, each collection having a single unimodal "normal" or "Gaussian" distribution curve. Most of the microparticles (e.g., at least 50%, 60%, 70% or 80% of the microparticles) may have an average particle size (D50) in the range of 1 to 50 microns (e.g., 1 to 10 microns), and a small amount of microparticles (e.g., less than 50%, 40%, 30% or 20% of the microparticles) may have a larger average particle size, such as an average particle size (D50) in the range of 50 to 100 microns or 10 to 99 microns.
[0043] According to other example films, the coarse layer may be made of a combination of granular micron particles and non-granular particles (e.g., including a combination of granular micron particles and non-granular particles, consisting of a combination of granular micron particles and non-granular particles, or consisting mainly of a combination of granular micron particles and non-granular particles). The non-granular particles include particles that are branched or dendritic or have an aspect ratio greater than 5 or greater than 10. Most of the micron particles (e.g., at least 50%, 60%, 70%, or 80% of the micron particles) may have a granular shape, and a small amount of the micron particles (e.g., less than 50%, 40%, 30%, or 20% of the micron particles) may have a non-granular shape, i.e., branched or dendritic or have an aspect ratio greater than 5 or greater than 10.
[0044] Non-limiting examples of metal particles that can be used as nanoparticles of the fine layer include metal particles made of any metal (including pure metals and alloys), such as stainless steel, another iron or steel alloy, nickel or nickel alloy, titanium or titanium alloy, etc. The sintering point of the nanoparticles is higher than the sintering point of the micron particles of the coarse layer.
[0045] The nanoparticles used to form the fine layer begin as a "collection" of nanoparticles, meaning a volume of individual solid nanoparticles having certain common general physical characteristics, such as shape, size, and chemical composition. The collection of particles is essentially dry and flowable, such as a "powder," where the particles can move relative to each other and where air spaces exist between particle surfaces. Most or all of the particles are similar or identical in composition, for example, made of a single type of metallic material, where the particle sizes fit a bell-curve shaped particle size distribution.
[0046] According to certain example films, the fine layer may be made of (e.g., include, consist of, or consist primarily of) a collection of particles that are all or substantially all nanoparticles and all or substantially all of a single type of metallic material. The nanoparticles may be, for example, stainless steel particles, e.g., particles that account for at least 80 wt%, 90 wt%, 95 wt%, 99 wt% of the total nanoparticles used to form the fine layer are made of stainless steel.
[0047] Nanoparticles can have a particle size distribution in the form of a "normal" or "Gaussian" distribution curve. Thus, a plot of the frequency of particles within a collection of particles (%, y-axis) versus the size (diameter) range of particles in the collection (x-axis, logarithmic scale) forms a bell-shaped curve. The curve is characterized by a particle size (diameter) distribution in the form of a continuous curve that is bell-shaped or approximately bell-shaped (e.g., Gaussian), with a minimum particle size at one end of the curve, a maximum particle size at the second end of the curve, a single peak (maximum) between the first and second ends, a continuous and gradually increasing curve between the first end and the single peak, and a continuous and gradually decreasing curve between the single peak and the second end.
[0048] The average particle size (D50) of the particles in the nanoparticle collection can be an average particle size useful in the filter layer. Examples of useful average particle sizes of nanoparticle collections can be less than 1 micron, for example, less than 500 nanometers, and preferably in the range of 10 to 150 or 200 nanometers. The particle size of fine particles can be measured using ASTM B822-17 (Standard Test Method for Particle Size Distribution of Metal Powders and Related Compounds by Light Scattering (for Particle Sizes <45 Micrometers)).
[0049] Examples of useful nanoparticles have a predominantly round or spherical shape with an aspect ratio of less than 3, less than 2, or less than 1.5.
[0050] The porous sintered membrane and its layers may have porosity characteristics that will allow the porous sintered body to be effectively used for the desired purpose, such as as a filtration membrane. For use as a filtration membrane, in particular to allow filtration of a fluid stream at a desired high flow rate, the described coarse layer may preferably have a porosity in the range of 10% to 30%, such as a porosity in the range of 10% to 20%. The fine layer of the membrane may have a porosity higher than that of the coarse layer, an example porosity value of the fine layer being at least 25%, such as in the range of 25% to 45% or 30% to 40%.
[0051] As used herein and in the porous sintered body field, the "porosity" (sometimes also referred to as "void fraction") of a porous sintered body is a measure of the percentage of void (i.e., "empty") space in a body to the total volume of the body, and is calculated as the fraction of the body void volume to the total volume of the body. A body with zero porosity is completely solid.
[0052] The sintered membrane may comprise the described coarse layers and fine layers (i.e., include, consist of, or consist primarily of coarse layers and fine layers). The total membrane thickness of the membrane and the relative thickness of its coarse and fine layers may be any useful value. The thickness of the coarse layer may provide support for the fine layers without unduly restricting fluid flow through the body. The thickness of the fine layers may provide the desired filtration performance and also provide good strength in the membrane, particularly in a tubular membrane.
[0053] The total thickness of the porous sintered membrane used as a filter membrane can be relatively thin, for example having a relatively small thickness, for example a micron-level thickness. Thin filter membranes can produce certain desired properties, including reducing mass and reducing the pressure drop on the filter during use. Examples of useful or preferred porous sintered membranes for filtering supercritical fluids such as supercritical carbon dioxide can have a thickness below 2000 or 1500 microns, for example from 800 or 1000 to 1200 or 1500 microns.
[0054] In the example of a porous sintered membrane, the coarse layer may be thicker or thinner than the fine layer, and preferably, may be thicker. According to some examples, the porous sintered membrane may have a coarse layer having a thickness of at least 50% of the total thickness of the membrane, for example, at least 55%, 60%, 70% or 80% of the total thickness of the membrane. The fine layer may have a thickness of less than 50% of the total thickness of the membrane, for example, less than 50%, 40%, 30%, 20% or 10% of the total thickness of the membrane.
[0055] Some more specific examples of multilayer films may have a coarse layer with a thickness in the range of 500 to 1000 microns, such as in the range of 600 to 900 microns. These films may also have a fine layer with a thickness less than 500 microns, such as in the range of 2 to 300 microns.
[0056] The porous film contains a coarse layer, a fine layer, and may optionally contain but not necessarily require other layers or materials. According to certain embodiments, the porous sintered body can be made to consist of a coarse layer and a fine layer or to consist mainly of a coarse layer and a fine layer. The porous sintered body "consisting mainly of a coarse layer and a fine layer" contains these two layers and no more than a negligible amount of any other layer or material, for example, no more than 5 wt%, 3 wt%, 1 wt%, 0.5 wt% or 0.1 wt% of any other layer or material.
[0057] A filtration membrane comprising, consisting of, or consisting essentially of the porous sintered membrane described may comprise a useful surface area through which fluid flows, which surface area may preferably be high enough to allow desired filtration performance characteristics during use, such as low pressure drop, a desired high bubble point, a desired high flow rate of fluid through the filter, and a useful removal efficiency (as reflected by LRV).
[0058] The exemplary porous sintered membrane can be formed into a filter membrane in the form of a flat sheet, or alternatively formed into a three-dimensional shape, such as a cup, a cone, an open tube (open at two opposite ends) or a closed end tube (also called a "closed cylinder", meaning a tube or cylinder with one closed end and one open end). A specific example of a filter body that can be used to filter supercritical carbon dioxide can be an open cylinder filter membrane, i.e., a tube, having a length in the range of 10 to 100 mm and a diameter in the range of 0.5 to 2 inches, such as in the range of 0.75 to 1.5 inches.
[0059] The porous membrane of the present specification can have a bubble point, which helps the body to effectively filter fluids, such as supercritical fluids, such as supercritical carbon dioxide. Examples of useful or preferred bubble points of the membrane can be at least 40, 50, 55 or 60 pounds per square inch measured by ASTM E128-99 and measured using isopropyl alcohol and water (60 / 40).
[0060] The bubble point is measured according to ASTM standard E-128 using isopropyl alcohol (IPA) as the test liquid. The material to be tested is completely soaked with the wetting solution and then placed in a fixture that seals its perimeter but leaves one surface visible and the other sealed. Air pressure is applied to the sealed side of the material. The pressure at which a bubble forms on the visible surface is recorded.
[0061] The porous membrane of this specification sheet can have flow characteristics, which means that fluid can be allowed to flow through the film, which is useful for allowing the film to effectively filter fluid (such as supercritical fluid, such as supercritical carbon dioxide). Flow velocity can be measured as the unit area flow rate of filter membrane under a given fluid pressure. The example of the useful or preferred flow velocity of the fluid by the film can be at least 0.10 or at least 0.12 or at least 0.15 standard liters per minute (slpm) per square centimeter, which is obtained using the air test under 30 pounds per square inch pressure.
[0062] The flow through the membrane can be measured by the air permeability test as shown below. The membrane to be tested is fixed in a closed housing and the air flow is controlled using a mass flow meter. The flow rate is adjusted until the inlet pressure (measured by a pressure gauge or sensor) reaches the specified value. Under the conditions of 20°C, an upstream pressure of 200kPag (2BARG) and a downstream pressure of 0kPag (0BARG) (i.e. atmospheric pressure), the air flow through the membrane with a known frontal area is measured and expressed in slpm / cm2 (unit area flow).
[0063] Figure 1 A side cross-sectional view of a portion of a multi-layer porous sintered membrane is schematically shown. The membrane 10 includes a coarse layer 20 made primarily or entirely of coarse particles 22. The membrane 10 also includes a fine layer 30 made primarily or entirely of fine particles 26. The sintered particles are interconnected at the particle surfaces (not shown) to form a metal matrix constituting the multi-layer porous sintered membrane.
[0064] Figure 2A , 2B and 2C are the Figure 1 Micrograph image of an example porous sintered membrane is schematically shown. Figure 2A and 2B Images of a multilayer porous sintered membrane 10 are shown at different magnifications. The membrane 10 includes a coarse layer 20 made entirely of coarse particles 22 and a fine layer 30 made entirely of fine particles 26. The sintered particles are interconnected at the particle surfaces to form a porous sintered membrane.
[0065] Figure 2C Shown at higher magnification Figure 2A and 2B The fine layer 30 (left) and the coarse layer 20 (right) of the membrane 10 are shown. Figure 2C A comparison of the different pore structures of the coarse layer 20 and the fine layer 30 is shown. In comparison, the coarse layer 20 has a smaller number of much larger pores and the fine layer 30 has a higher number of much smaller pores. The fine layer 30 also has a higher porosity than the coarse layer 20.
[0066] Figure 3A and 3B This manual is Figure 1 Micrograph image of an example porous sintered membrane is schematically shown. Figure 3A and 3B Images of a multilayer porous sintered membrane 10 are shown at different magnifications. The membrane 10 comprises a coarse layer 20 made of a mixture of coarse particles 22 having different particle sizes (50 to 100 microns and 2 to 3 microns), and a fine layer 30 made entirely of fine particles 26. Figure 3A Two layers are shown, and Figure 3B Only the coarse layer 20 is shown and at a lower magnification.
[0067] The example of described porous sintered membrane can be used as filter membrane, to remove particles or pollutants from the fluid flow through filter membrane.Fluid can be any type of fluid, including gas, liquid or supercritical fluid.Fluid can be any fluid that needs to be filtered, including superfluid carbon dioxide as a specific example, which contains low-level impurities from any source.Supercritical carbon dioxide can be used for processing or manufacturing semiconductors and microelectronic devices.Porous sintered body can effectively remove pollutants from fluid flow by screening or non-screening filtering mechanism or both.When fluid is supercritical carbon dioxide, filtration can be mainly carried out by non-screening filtering mechanism.
[0068] The pressure of the fluid processed by the filtration system during the step of filtering the fluid using the described filtration membrane can be a desired pressure. For methods and apparatus for filtering certain types of fluids (including supercritical carbon dioxide), the fluid pressure within the filtration system, such as the fluid pressure when the fluid passes through the filter membrane, is relatively high, such as at least 10, 20, or up to or in excess of 30 MPa.
[0069] The pressure differential (or "pressure drop") across the thickness of the described filter membrane (between the upstream side of the filter and the downstream side of the filter) during use of the filter membrane can be any pressure differential that achieves the desired effect (e.g., particle retention and flow rate) in the filtration process and is commercially feasible. For use in filtering supercritical carbon dioxide at elevated pressures, the pressure differential across the filter membrane can be at least 1, 2, or 3 megapascals (MPa).
[0070] The amount of fluid flowing through the filtration membrane during the filtration step (volume per pass through the filter) may be an amount that achieves a desired effect (eg, particle retention rate) in the filtration step and is commercially feasible.
[0071] The temperature of the fluid stream passing through the described filtration membranes may be any temperature that achieves commercially effective filtration.For filtering supercritical carbon dioxide, the temperature may be relatively high, such as a temperature of at least 100, 150 or 200 degrees Celsius.
[0072] The described sintered membrane can be manufactured by the following multi-step process: forming a precursor containing a first layer made essentially or entirely of the said micronized particles, forming a second layer made essentially or entirely of the said nanoparticles on the surface of the first layer, and then sintering the precursor (made of the first layer and the second layer) so that the particles of the layers are bonded together to form a multi-layer porous sintered membrane.
[0073] In certain example methods, the precursor can be formed by a dry method using a dry powder of metal particles without any polymer or other liquid component in the powder. The first layer of the precursor can be formed by molding the first layer from a first dry powder, the first dry powder comprising at least a major portion of the described micron particles (including the micron particles, consisting of the micron particles, or mainly consisting of the micron particles), for example, using an isotactic molding technique to form a first layer of green body. The precursor can be formed by molding the particles and applying pressure to the molded particles in an amount of at least 5,000 pounds per square inch gauge (psig) (e.g., at least 8,000, 10,000, or at least 15,000 psig).
[0074] After forming the first layer of green body, a dry powder containing (including, consisting of, or mainly consisting of) nanoparticles (made entirely or almost entirely of nanoparticles) is uniformly applied to the surface of the first layer of green body and pressed against the surface again by isotactic molding techniques. The nanoparticles are pressed against the first layer of green body at a pressure lower than that used to compress the first layer of green body, for example, a pressure of less than 5,000 pounds per square inch gauge (psig), for example, less than 2,000 psig, or less than 1,500 psig, or less than 1,000 psig.
[0075] The resulting green body having a first (coarse) layer and a second (fine) layer is then sintered to produce the described sintered porous body having a coarse layer and a fine layer. Each of the green body and its two separate layers can consist of or mainly consist of a compressed layer generated from a powder, and does not require or contain any other materials, such as polymers (binders), surfactants, solvents, etc.
[0076] In more detail, according to an exemplary step, a collection of particles in the form of a dry powder mainly or completely containing coarse particles (consisting of or mainly consisting of coarse particles) is molded at a pressure of at least 5,000psig to compress the particles to form a film in the form of, for example, a small tube. By a technique, the molding step can be a type known as isotactic molding or isotactic wet compression molding. (See, for example, U.S. Patent 7,534,287, the entire contents of which are incorporated herein by reference.) The produced film mainly or completely contains coarse particles compressed together by the molding step, and will become the first layer of the porous sintered film. The film is held together by the contact generated between the particles, which is generated by the compression of the particles. This film is referred to as a "precursor" or "green body", specifically a "first layer precursor" here, which is self-supporting but fragile.
[0077] The second particle set mainly or completely contains fine particles (consisting of fine particles or mainly consisting of fine particles), i.e., nanoparticles. This particle set is applied to a surface of the first layer precursor, for example, to the outer surface of the first layer precursor in the form of a tube. The nanoparticles are applied in a manner that a consistent and uniform amount of nanoparticles are placed on the surface of the first layer precursor. Effective methods for applying nanoparticles to surfaces are known and include methods known as "air laying" techniques, such as placing a screen or wire mesh on the surface of the first layer, and then passing the nanoparticles through the screen, optionally using a brush to evenly distribute the particles.
[0078] After the nanoparticles are uniformly placed on the surface of the first layer, the resulting body is molded again under pressure to press the nanoparticles against the first layer and form a second layer compressed on the surface of the first layer. The amount of pressure applied to the nanoparticles placed on the first layer is less than 5,000 psig, such as less than 2,000 psig, or less than 1,000 psig. Molding and compression of the nanoparticles onto the surface of the first layer can be performed by isotactic molding techniques, such as isotactic wet compression molding techniques. The resulting precursor ("green body") contains a compressed and unsintered first layer made of coarse particles and a compressed and sintered second layer made of nanoparticles.
[0079] In a subsequent step, the precursor is sintered at a sintering temperature that will effectively combine the particles of the two layers into a single porous multilayer sintered membrane. During the sintering process, the fine particles of the fine layer and the coarse particles of the coarse layer will preferably experience similar levels of sintering and similar sintering shrinkage, which can make the sintered membrane stable and prevent the membrane from cracking and deforming during sintering.
[0080] The filter membrane may be included in a filtration system or device including a filter housing that houses and supports the filter membrane at a location where fluid flows to allow fluid to flow through the membrane as the fluid passes through the filter housing. The filter housing may have an inlet, an outlet, and an internal volume containing the filter membrane.
[0081] Example of filter housing (cross section) Figure 4 The example filter housing 100 includes a housing body 110, a fluid inlet 112, a fluid outlet 114, and an interior 120. A tubular multi-layer porous sintered membrane 130 is included in the interior 120, such as by being welded to the housing base 124 at weld points 130. In use, a fluid (not shown) flows into the inlet 112, through the filter membrane 130, through the interior 120, and exits the filter housing through the outlet 114 as indicated by the arrows.
[0082] Example 1
[0083]
[0084] Example membranes made according to the present disclosure may exhibit relatively high bubble points (due to relatively small pore sizes) and have relatively high flow levels through the membranes compared to existing commercially available products.
[0085] Example 1 is a porous sintered filtration membrane as described herein. The membrane contains a coarse layer made of nickel particles having an average size (diameter) in the range of 2 to 3 microns and having a porosity in the range of 10% to 20%. The membrane contains a fine layer made of stainless steel nanoparticles and having a higher porosity than the coarse layer, for example, a porosity in the range of 30% to 40%.
[0086] Examples A and B are tubular porous membranes made based on the description of U.S. Pat. No. 7,534,287. Examples A and B are made from nickel particles that include fine dendritic particles and nanoparticles, but do not include coarse particles (as that term is used herein). The membranes of Examples A and B include an inner layer made only from fine dendritic nickel particles and an outer layer made from a blend of fine dendritic nickel particles and nickel nanoparticles.
[0087] Example 2
[0088] A tubular rubber isostatic pressing mold with an outer diameter of 2.1 cm, an inner steel mandrel diameter of 1.9 cm and a length of 17 cm was filled with 2-3 micron Ni powder (reference VALE Ni 255 type). The filled mold was isostatically pressed with a pressure of 10,000 pounds per square inch. After the powder was compressed, an annular space was present between the rubber mold and the compact (precursor) still on the steel mandrel. This annular space was then filled with a stainless steel nanopowder (reference: Sky Springs-0964XH) with a diameter of 60-150 nanometers and pressed at 1,000 psi.
[0089] The 2-layer compact was removed from the mold and the central steel mandrel was removed. The compact was placed in a vacuum / hydrogen furnace and sintered at 1010°C for 60 minutes.
[0090] A portion of the sintered tube was cut into 15 mm and subjected to a radial squeeze test. The outer layer of the tube began to crack at a "K" value of 39 KSI. A 104 mm long sintered tube was cut and the flow rate was measured. It had an air flow rate of 0.13 slpm / cm^2 at 30 psi. The bubble point measured in 60 / 40 IPA / water was 80 psi.
[0091] Evaluation of the porosity of the nano (fine) layer and the coarse layer showed that the nano (fine) layer was 230 microns thick with a porosity of 27% and the coarse layer was 700 microns thick with a porosity of 17%.
[0092] Membrane Figure 2A , 2B and 2C.
[0093] Example 3
[0094] A tubular rubber isostatic pressing mold with an OD of 2.1 cm, an inner steel mandrel diameter of 1.9 cm, and a length of 17 cm is filled with a blend of 70% by mass of 2-3 micron Ni powder (reference VALE Ni 255 type) and 30% by mass of 50-100 micron Ni powder. The filled mold is isostatically pressed at 12,000 psi. The annular space is filled with stainless steel nanopowder with a diameter of 60-150 nanometers (reference: Sky Springs-0964XH) and pressed at 1,000 psi. The 18mm radial extrusion "K" value is 38 KSI, the 60 / 40 IAP / water bubble point is 70 psi, and the air flow / unit area at 30 psi is 0.17 slpm / cm^2.
[0095] Evaluation of the porosity of the nano (fine) layer and the coarse layer showed that the nano (fine) layer was 250 microns thick and had a porosity of 35%, and the coarse layer was 800 microns thick and had a porosity of 16%. Figure 3A and 3B shown.
[0096] aspect
[0097] Aspect 1. A multilayer porous sintered membrane, comprising: a coarse layer, comprising sintered micronized particles, the micronized particles having a micronized particle sintering point, and the coarse layer having a coarse layer porosity; and a fine layer, comprising sintered nanoparticles, the nanoparticles having a nanoparticle sintering point, the fine layer having a fine layer porosity, the nanoparticle sintering point being greater than the microparticle sintering point, and the fine layer porosity being greater than the coarse layer porosity.
[0098] Aspect 2. The membrane of aspect 1, wherein the membrane is tubular and the coarse layer is an inner layer.
[0099] Aspect 3. The membrane according to aspect 1 or 2, wherein the coarse layer porosity is in the range of 10% to 30%.
[0100] Aspect 4. The membrane according to any one of aspects 1 to 3, wherein the fine layer porosity is in the range of 25% to 45%.
[0101] Aspect 5. The film according to any one of aspects 1 to 4, wherein the sintered nanoparticles are formed of nanoparticles having an average size in the range of 10 to 200 nanometers.
[0102] Aspect 6. The film of any one of aspects 1 to 5, wherein the fine layer comprises at least 90 weight percent of sintered nanoparticles based on the total weight of the fine layer.
[0103] Aspect 7. The film according to any one of aspects 1 to 6, wherein the sintered microparticles are formed of microparticles having an average size in the range of 1 to 100 microns.
[0104] Aspect 8. The film according to any one of aspects 1 to 7, wherein:
[0105] The sintered micron particles are nickel or a nickel alloy comprising at least 90% by weight of the total weight of the sintered coarse particles, and
[0106] The sintered nanoparticles are stainless steel in an amount of at least 90 weight percent of the total weight of the sintered nanoparticles.
[0107] Aspect 9. The membrane of any one of aspects 1 to 8, having a bubble point of at least 50 psi as measured by ASTM E218-99 using isopropyl alcohol and water (60 / 40).
[0108] Aspect 10. The membrane of any one of aspects 1 to 9, having a flow rate per unit area of at least 0.10 (measured at 30 psi-slpm / cm2).
[0109] Aspect 11. The film according to any one of aspects 1 to 10, wherein:
[0110] The film has a thickness in the range of 500 to 1500 microns,
[0111] The coarse layer has a thickness in the range of 500 to 1200 microns, and
[0112] The thin layer has a thickness in the range of 2 to 400 microns.
[0113] Aspect 12. A filter assembly comprising a filter housing containing the membrane according to any one of aspects 1 to 11.
[0114] Aspect 13. A method for treating supercritical carbon dioxide, the method comprising passing the supercritical carbon dioxide through the membrane according to any one of aspects 1 to 11.
[0115] Aspect 14. The method according to aspect 13, wherein the pressure difference across the membrane is at least 1 MPa.
[0116] Aspect 15. A method comprising:
[0117] The micron particles are compressed into a coarse layer using a first compression pressure, the micron particles having micron particle sintering points, and
[0118] forming a fine layer on the coarse layer by applying nanoparticles to the coarse layer and compressing the nanoparticles using a second compressing pressure lower than the first compressing pressure to form a precursor including the coarse layer and the fine layer,
[0119] The nanoparticles have a nanoparticle sintering point greater than a sintering point of the microparticles.
[0120] Aspect 16. The method of aspect 15, wherein the first compression pressure is at least 5,000 psi.
[0121] Aspect 17. The method according to aspect 15 or 16, wherein the second compression pressure is less than 1,500 psi.
[0122] Aspect 18. The method according to any one of aspects 15 to 17, wherein the precursor is tubular, the coarse layer is an inner layer, and the fine layer is an outer layer.
[0123] Aspect 19. The method according to any one of aspects 15 to 18, wherein the nanoparticles have an average size in the range of 10 to 200 nanometers.
[0124] Aspect 20. The method according to any one of aspects 15 to 19, wherein the stratum comprises at least 90 weight percent of nanoparticles based on the total weight of the stratum.
[0125] Aspect 21. The method according to any one of aspects 15 to 20, wherein the microparticles have an average size in the range of 1 to 100 microns.
[0126] Aspect 22. The method according to any one of aspects 15 to 21, wherein:
[0127] The micronized particles are nickel or nickel alloys accounting for at least 90% by weight of the total weight of the coarse particles, and
[0128] The nanoparticles are stainless steel accounting for at least 90 weight percent of the total weight of the nanoparticles.
[0129] Aspect 23. A method according to any one of Aspects 15 to 22, comprising sintering the precursor at a sintering temperature, wherein the sintering temperature causes the sintering of the micronized particles and the sintering of the nanoparticles to form a multilayer porous sintered membrane, wherein the multilayer porous sintered membrane includes a coarse layer comprising the sintered coarse particles and a fine layer comprising the sintered nanoparticles.
[0130] Aspect 24. The method according to aspect 23, wherein the coarse layer has a coarse layer porosity, and the fine layer has a fine layer porosity greater than the coarse layer porosity.
[0131] Aspect 25. The method according to aspect 23 or 24, wherein the coarse layer porosity is in the range of 10% to 30%.
[0132] Aspect 26. The method according to any one of aspects 23 to 25, wherein the fine layer porosity is in the range of 25% to 45%.
[0133] Aspect 27. The method according to any one of aspects 23 to 26, wherein the multi-layer porous sintered membrane has a bubble point of at least 50 pounds per square inch as measured by ASTM E218-99 and measured using isopropyl alcohol and water (60 / 40).
[0134] Aspect 28. The method according to any one of aspects 23 to 27, wherein the multi-layer porous sintered membrane has a flow rate per unit area of at least 0.10 (measured at 30 psi-slpm / cm2).
[0135] Aspect 29. The method according to any one of aspects 23 to 28, wherein:
[0136] The multi-layer porous sintered membrane has a thickness in the range of 500 to 1500 micrometers,
[0137] The first layer has a thickness in the range of 500 to 1200 microns, and
[0138] The second layer has a thickness in the range of 2 to 400 microns.
Claims
1. A multilayer porous sintered membrane, characterized in that The multilayer porous sintered membrane comprises: A coarse layer comprising sintered micron-particles, the micron-particles having micron-particle sintering points, the coarse layer having a coarse layer porosity, and The fine layer comprises sintered nanoparticles, wherein the nanoparticles have nanoparticle sintering points, the fine layer has a fine layer porosity, the nanoparticle sintering points are greater than the micron particle sintering points, and the fine layer porosity is greater than the coarse layer porosity.
2. The multilayer porous sintered membrane according to claim 1, characterized in that The multi-layer porous sintered membrane is tubular, and the coarse layer is an inner layer.
3. The multilayer porous sintered membrane according to claim 1 or 2, characterized in that The coarse layer porosity is in the range of 10% to 30%.
4. The multilayer porous sintered membrane according to claim 1 or 2, characterized in that The fine layer porosity is in the range of 25% to 45%.
5. The multilayer porous sintered membrane according to claim 1 or 2, characterized in that The sintered nanoparticles are formed of nanoparticles having an average size in the range of 10 to 200 nanometers.
6. The multilayer porous sintered membrane according to claim 1 or 2, characterized in that The fine layer includes at least 90 weight percent of sintered nanoparticles based on the total weight of the fine layer.
7. The multilayer porous sintered membrane according to claim 1 or 2, characterized in that The sintered micron particles are formed of micron particles having an average size in the range of 1 to 100 microns.
8. The multilayer porous sintered membrane according to claim 1 or 2, characterized in that: The sintered micron particles are nickel or nickel alloys accounting for at least 90 weight % of the total weight of the sintered coarse particles, and the sintered nanoparticles are stainless steel accounting for at least 90 weight % of the total weight of the sintered nanoparticles.
9. The multilayer porous sintered membrane according to claim 1 or 2, characterized in that The multi-layer porous sintered membrane has a bubble point of at least 50 psi as measured by ASTM E218-99 using isopropyl alcohol and water.
10. The multilayer porous sintered membrane according to claim 1 or 2, characterized in that The multi-layer porous sintered membrane has a flow rate per unit area of at least 0.10, wherein the flow rate per unit area is measured at 30 psi-slpm / cm2.
11. The multilayer porous sintered membrane according to claim 1 or 2, characterized in that: The multi-layer porous sintered membrane has a thickness in the range of 500 to 1500 micrometers, The coarse layer has a thickness in the range of 500 to 1200 microns, and The thin layer has a thickness in the range of 2 to 400 microns.
12. A filter assembly, characterized in that The filter assembly comprises a filter housing containing a multi-layer porous sintered membrane according to any one of claims 1 to 11.
Citation Information
Patent Citations
Porous sintered composite materials
US7534287B2
Cited By
Sintered porous body having multiple layers
CN118023526A